Saccharomyces boulardii to Prevent Antibiotic-Associated Diarrhea: A Randomized, Double-Masked, Placebo-Controlled Trial. (29th January 2016) - Ehrhardt, Stephan; Guo, Nan; Hinz, Rebecca; Schoppen, Stefanie; May, Jürgen; Reiser, Markus; Schroeder, Maximilian Philipp; Schmiedel, Stefan; Keuchel, Martin; Reisinger, Emil C.; Langeheinecke, Andreas; de Weerth, Andreas; et al.
Abstract : Antibiotic-associated diarrhea is an important clinical problem, associated with morbidity, mortality and healthcare costs. Our randomized, placebo controlled multicenter trial do not support the efficacy of Saccharomyces boulardii in the prevention of antibiotic-associated diarrhea. Abstract: Background.  Antibiotic-associated diarrhea (AAD) and Clostridium difficile -associated diarrhea (CDAD) are common complications of antibiotic use. Data on the efficacy of probiotics to prevent AAD and CDAD are unclear. We aimed to evaluate the efficacy of Saccharomyces boulardii to prevent AAD and CDAD in hospitalized adult patients. Methods.  We conducted a multicenter, phase III, double-masked, randomized, placebo-controlled trial in hospitalized patients who received systemic antibiotic treatment in 15 hospitals in Germany between July 2010 and October 2012. Participants received Perenterol forte 250 mg capsules or matching placebo twice per day within 24 hours of initiating antibiotic treatment, continued treatment for 7 days after antibiotic discontinuation, and were then observed for 6 weeks. Results.  Two thousand four hundred forty-four patients were screened. The trial was stopped early for futility after inclusion of 477 participants. Two hundred forty-six patients aged 60.1 ± 16.5 years and 231 patients aged 56.5 ± 17.8 were randomized to the S boulardii group and the placebo group, respectively, with 21 and 19 AADs in the respective groups ( P = .87). The hazard ratio of AAD in the S boulardii group compared with the placebo group was 1.02 (95% confidence interval, .55–1.90; P = .94). Clostridium difficile -associated diarrhea occurred in 0.8% of participants (4 of 477). Nine serious adverse events were recorded in the S boulardii group, and 3 serious adverse events were recorded in the placebo group. None were related to study participation. Conclusions.  We found no evidence for an effect of S boulardii in preventing AAD or CDAD in a population of hospitalized patients without particular risk factors apart from systemic antibiotic treatment. ClinicalTrials.gov Identifier.  NCT01143272.